The role of manufacturer brands in the face of social demands. Analysis of “Negrita” re-branding advertising by Alicorp - Rivas Gonzales, Viviana Lorena (2020)
Based on the analysis of Alicorps’ official statement regarding the renaming of their commercial brand Negrita, this article suggests delving into the reasons why brands have begun to take political stands through their discourse and actions, and how this decisions have an impact on the commercial and manufacturers’ brand equity as well as their consumers. Albeit interest regarding role portrayals in advertising is not a new issue,  “¿is it possible that brands and advertising have embraced a new role as social actors?, “¿are societal changes so powerful that they call for a brand to take a political stand towards them?”  Through on the outcome of these questions, and through this cases’ discussion, this study seeks to explore the roots and consequences of this new brand positioning.